REIMPLANTATION IN CASE OF MARGINAL PERIODONTITIS - OPPORTUNITY IN ORAL REHABILITATION - Sergiu Ciobanu; Sofia Sirbu; Vasile Cirimpei; Tatiana Cirimpei; Ana Ciobanu (Romanian Dental Association for Education, 2013)
Stomatology had a big push thru in the latest 100 years. Especially in clinical solving of edentulism with fixed methods by the means of endooseos implants, although their usage was introduced by the Maya tribes 1350 years before the first titanium implants proposed by Branermark, representing shells which were endooseosly implantated which presented radiological compact bone formation around them. But a more interesting topic is represented by the autotransplantation. The proper re-implantation was performed 4 days after the surgery and general treatment (14 days cure). Anaesthesia with 4% Ubistezine by 1,7 ml being deposited infiltrative in 22 nd 14 teeth region. Then the splint that was placed in the region of missing tooth has been sectioned and the vertical incisions have been performed and intrasulcular decollating a trapezoid muco- periostal flap from 23 to 15, including re-implanting zone. The minutious curettage on open field has been performed on the entire intervention zone, the pathological tissues and granulations were collected and preserved in 2,5 % glutaraldehyde, for the following electronic microscopy. The remaining alveolar parts-have been curetted in order to produce hemorrhage and the internal cortical has been forated pointed for a better osteoplastic material integration(LitAr).